Synergistic photobiomodulation with 808-nm and 1064-nm lasers to reduce the β-amyloid neurotoxicity in the in vitro Alzheimer's disease models - Zhang, Renlong; Zhou, Ting; Samanta, Soham; Luo, Ziyi; Li, Shaowei; Xu, Hao; Qu, Junle (Frontiers in Neuroimaging, 2022)
Background: In Alzheimer's disease (AD), the deposition of β-amyloid (Aβ) plaques is closely associated with the neuronal apoptosis and activation of microglia, which may result in the functional impairment of neurons through proinflammation and over-pruning of the neurons. Photobiomodulation (PBM) is a noninvasive therapeutic approach without any conspicuous side-effect which has shown promising attributes in the treatment of chronic brain diseases such as AD by reducing the Aβ burden. However, neither the optimal parameters for PBM treatment, nor its exact role in modulating the microglial functions/activities have been conclusively established yet. Methods: An inflammatory stimulation model of Alzheimer's disease (AD) was set up by activating microglia and neuroblastoma with fibrosis β-amyloid (fAβ) in Transwell insert system. SH-SY5Y neuroblastoma cells and BV2 microglia cells were irradiated with 808 nm and 1064 nm lasers respectively (Power density of 50 mW/cm2, dose of 10 J/cm2) to study the PBM activity. The amount of labeled fAβ phagocytosed by microglia was considered to assess the microglial phagocytosis. PBM-induced neuroprotective study was performed with the AD model under different laser parameters to realize the optimal condition. Microglial phenotype, microglial secretions of the pro-inflammatory and anti-inflammatory factors as well as the intracellular Ca2+ levels in microglia were studied in details to understand the structural and functional changes occurring in the microglia cells of AD model upon PBM treatment. Conclusions: Synergistic PBM effect (with 808 nm and 1064 nm lasers) effectively inhibited the fAβ-induced neurotoxicity of neuroblastoma by promoting the viability of neuroblastoma and regulating the intracellular Ca2+ levels of microglia. Moreover, downregulation of Ca2+ led to microglial polarization with M2 phenotype, which promote the fAβ phagocytosis, and resulted in the up-regulated expression of anti-inflammatory factors and down-regulated expression of inflammatory factors.